Modern technologies in artistic ceramics (Texas Journal of Multidisciplinary Studies, 2022)
Badi ceramics have endless aesthetic and functionalcapabilities. Its artistic and technical qualities can be used in architecture, monumental and decorative art, sculpture and designn. A rich historical experience convinces us that ceramism is subject to solving complex problems of synthesis with architecture. In modern art, the desire for a variety of materials used for all artists is more pronounced in t obora